Microstructure and hot corrosion performance of stainless steel 347 produced by wire arc additive manufacturing. (April 2023) - Kannan, A. Rajesh; Rajkumar, V.; Prasad, C. Durga; Shanmugam, N. Siva; Yoon, Jonghun
Abstract: The present work reports the feasibility of wire arc additive manufacturing (WAAM) process to manufacture SS 347 components for high temperature applications. The microstructure of WAAM processed SS 347 (WAAM 347) comprised of austenite and residual delta-ferrite while the ferrite fraction varied between 1.40 and 4.20% along the building direction. Cyclic hot corrosion behaviour of WAAM 347 specimens were investigated under the Na2 SO4 –60%V2 O5 molten salt at 700 °C by measuring the weight change. Higher weight gain was noticed in the samples exposed to hot corrosion because of the deposition of molten salt mixture. X-ray diffraction results revealed the formation of oxides like Fe2 O3, FeV2 O4, and Ni3 V2 O8 while the presence of NiCr2 O4 and Cr2 O3 lowers the corrosion rate at elevated temperatures. The absence of spallation due to the good adherence of oxide-scales highlights that WAAM 347 structures are suitable for elevated temperature applications. Highlights: Stainless steel 347 was successfully fabricated by wire arc additive manufacturing. Microstructure comprised of austenite and residual delta-ferrite (1.40–4.20%). WAAM 347 is corrosion resistant in Na2 SO4 –60% V2 O5 salt environment at 700 °C. Oxides like Fe2 O3 and FeV2 O4 were dominant in hot corroded WAAM 347 surfaces. The presence of NiO, Cr2 O3, and NiCr2 O4 provided good corrosion resistance.